2023
DOI: 10.1002/adfm.202213843
|View full text |Cite
|
Sign up to set email alerts
|

Side‐Chain Methylthio‐Based Position Isomerism of Hole‐Transport Materials for Perovskite Solar Cells: From Theoretical Simulation to Experimental Characterization

Abstract: Hole transporting materials (HTMs) are imperative for promoting the development of perovskite solar cells (PSCs). Herein, three isomers of RQ4, RQ5, and RQ6 are constructed by methylthio (-SMe) group in the para, meta, and adjacent sites of terminal benzene on the side-chain of carbazole-arylamine derivatives based HTMs, and investigated by means of the theoretical simulation and experimental characterization. As a result of the theoretical simulation, the isomeric HTMs of RQ4-RQ6 exhibit appropriate highest o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…In our previous works, the B3P86/6-311G(d,p) method output a credible HOMO level in comparison with the experimental results. 46,47 According to Fig. 2c and d, it was found that the contribution of the LUMO for the pyrene group of CY2 (99.16%) was larger than that for the naphthalene group of CY1 (97.43%).…”
Section: Resultsmentioning
confidence: 95%
“…In our previous works, the B3P86/6-311G(d,p) method output a credible HOMO level in comparison with the experimental results. 46,47 According to Fig. 2c and d, it was found that the contribution of the LUMO for the pyrene group of CY2 (99.16%) was larger than that for the naphthalene group of CY1 (97.43%).…”
Section: Resultsmentioning
confidence: 95%
“…The dense and uniform morphology of the Py-DB film is beneficial for interfacial contact, and thus could facilitate charge transfer at the perovskite/HTM interface. [36][37]…”
Section: Resultsmentioning
confidence: 99%
“…Although the PCE of the champion device was not as good as the device based on the traditionally doped spiro-OMeTAD (Figure S10, Supporting Information), the over 22% efficiency was in the top-performing levels for normal structured devices based on dopant-free HTMs reported to date (Table S1, Supporting Information). [14][15][16][17][18][19]24,39,[46][47][48][49][50][51] To confirm the reliability of our sunlight simulator, external quantum efficiency (EQE) spectra were collected (Figure 4c). Both devices showed similar EQE response and high EQE value in the range of 350-800 nm.…”
Section: Resultsmentioning
confidence: 99%